No More Secrets? De-monopolizing Intelligence - Vrist Rønn, Kira; Ördén, Hedvig ; 0000-0002-5778-0824 (Canadian Foreign Policy Journal, 2025)
Intelligence scholars have described the contemporary availability of Open-Source Intelligence (OSINT) and the entrance of civil society actors into the field of intelligence as a “democratization of intelligence”, thereby portraying a fundamentally positive and inclusive enterprise. Assessing the implications of the recent explosion of OSINT groups and activists for traditional state intelligence actors, this chapter instead introduces the concept of de-monopolization. A turn to de-monopolization brings attention to the competitive aspects arising when civil society actors enter the field of intelligence. The chapter outlines two different forms of competition currently affecting state intelligence actors: a competition for insights and a competition for epistemic authority. Describing these contemporary tendencies and their impact on state intelligence work, the chapter then discusses how an increase in OSINT by civil society actors generates new tasks for intelligence actors, introduces new ideals, and pushes state intelligence agencies to defend their expertise in public.